Kinetic/Equilibrium Adsorption and Biodegradation-Incorporated Numerical Modeling for Reactive Capping in Nutrient-Contaminated Lake Sediments - Park, Seong Jik; Lee, Chang Gu (Korean Journal of Chemical Engineering, 2024)
A one-dimensional contaminant transport model coupled with adsorption and degradation processes was validated by capping incubation experiments that simulated nitrogen and phosphorus release from lake sediments. The model integrated advective–diffusive transport through sediment and capping materials by incorporating kinetic and equilibrium adsorption and microbial degradation. The results aligned well with the experimental data for dissolved oxygen (DO) and chemical oxygen demand (COD) under capping conditions. The model accurately predicted NH4–N concentration variations based on the capping material’s adsorption capacity. The NH4–N concentrations were negligibly impacted (< 10−7 mg/L) by zeolite kinetic adsorption rate; whereas, the equilibrium adsorption parameters, including the maximum capacity and Langmuir constant, significantly influenced them; they were more sensitive to lower maximum adsorption capacities and higher Langmuir constant ranges. The maximum specific growth rates of heterotrophic aerobes and nitrifiers affected the relatively NH4–N concentration minimally. However, COD concentrations were sensitive to the maximum specific growth rate of heterotrophic aerobes, which affected the DO concentration in the overlying water. Variations in the ammonium half-saturation constant affected neither of COD, NH4–N, NO3–N, or DO concentrations. The proposed model enhances the understanding and prediction of nutrient fate and transport in capping systems compared with that from conventional models.
Keywords: Adsorption capacities; Capping materials; Chemical-oxygen demands; Dissolved oxygen concentrations; Equilibrium adsorption; Lake sediments; Langmuir constant; Maximum specific growth rates; Monod type; Sediment capping; Chemical oxygen demand; Monod type; Nitrogen; Phosphorus; Sediment capping